Bangladesh : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses three main issues: bank lending rates, impact of climate change on the economy of Bangladesh, and financial inclusion in Bangladesh. According to international standards, average bank lending rates and interest rate spreads in Bangladesh are not high. Various prudent policies have been implemented to bring interest rates down further. Bangladesh is considered among the top countries in the world for vulnerability to climate change, because of its geographical location and topography. The Bangladesh government has taken a number of initiatives to expand financial inclusion in the country. Financial inclusion helps increase the incomes of financially marginalized members of a society.